Comparison of the Tissue Receptors for Vibrio cholerae and Escherichia coli Enterotoxins by Means of Gangliosides and Natural Cholera Toxoid - Holmgren, Jan (1973)
The in vitro binding properties of enterotoxins of Vibrio cholerae and Escherichia coli to different pure gangliosides and related neutral glycosphin-golipids were analyzed with a sorbent assay utilizing plastic tubes to which the glycolipid substances had been coupled. It was found that the cholera toxin bound to G(M1) ganglioside better than to the other tested substances G(M3), G(M3)-NGN, G(M2), G(D1a), G(D1b), G(T), G(A1), tetrahexoside-GlcNac and globoside. With this assay using G(M1)-coated tubes it is possible to measure cholera toxin even at concentrations below 1 ng/ml. Also enterotoxin of various E. coli strains bound to G(M1), but the affinity was much less than for cholera toxin. The G(M1) ganglioside, in contrast to the other glycosphingolipids, effectively inactivated cholera toxin as determined with the intradermal and the ileal loop assays; approximately equimolar concentrations of the ganglioside in relation to toxin sufficed. Also, the skin and ileal loop activities of E. coli enterotoxins could be inhibited by G(M1); however, several orders more of the ganglioside were required for such inhibition than for inactivation of the cholera toxin, and the differences between G(M1) and the other substances were less pronounced for E. coli toxins. Preincubation of rabbit ileal loops with choleragenoid, a natural toxoid of V. cholerae which has binding properties to the G(M1) ganglioside similar to cholera toxin, made the loops resistant to subsequently added enterotoxin of V. cholerae. The responsiveness to enterotoxin of E. coli was not reduced by this toxoid. A likely interpretation of these data is that the G(M1) ganglioside constitutes or at least contains the structure of functional tissue receptors for the cholera toxin, whereas the weak binding to G(M1) by E. coli enterotoxins is probably a pathogenetically insignificant reflection of structural similarities between these toxins and cholera toxin. Consequently, the cholera toxoid by occupying functional intestinal G(M1) receptors for the cholera toxin could inhibit the ileal response to this toxin, but not the response to E. coli enterotoxin since the intestinal receptors for the latter toxin are not affected by the cholera toxoid.